The Effect of Audit Tenure, Audit Delay, and Financial Distress on Going Concern Audit Opinion - Lia, Devi; Nurlaili, Nurlaili; Ningsih, Nur Wahyu (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
This study aims to analyze the effect of audit tenure, audit delay, and financial distress on the acceptance of going concern audit opinions in companies. The population in this study was textile and garment companies listed on the Indonesia Stock Exchange (IDX) in 2021-2024. The number of textile and garment companies listed on the IDX in 2021-2024 was 21. A sample of 17 companies with 68 data points was obtained using a purposive sampling method with predetermined research criteria. The results of the study indicate that partially audit delay and financial distress have an effect on going concern audit opinions, while audit tenure does not have a significant effect. The conclusion of this study is that the company’s financial condition is the main factor considered by auditors in issuing a going concern audit opinion. This study contributes to the literature by providing empirical evidence in the context of the textile and garment industry in Indonesia, particularly in the post-pandemic period, and by reinforcing the importance of financial distress as a key determinant in auditors’ decision-making. In addition, this research offers practical implications for auditors, management, and investors in assessing business continuity risks and improving the quality of audit judgments.